Identification of potential common cyclic-di-GMP regulated biomarkers among three gram negative bacteria via transcriptomic and metabolomic profiling - Cai, Zhao (2017)
Bacterial cells can switch between two life styles, namely planktonic and biofilm, depending on different environmental cues. Biofilms are involved in almost 80% of microbial infections. Biofilm infections can evade host immune attack and develop into chronic conditions, which cannot be efficiently eradicated by conventional antimicrobial treatments. In most Gram-negative bacteria, biofilm formation can be regulated by a secondary messenger, bis-(3'-5')-cyclic dimeric guanosine monophos-phate, c-di-GMP.